The efficiency of public support to private charity: An econometric analysis of the income tax treatment of charitable - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
Economists like to justify public redistributive activity with standard externality arguments. While not denying the existence of a private charity market based on altruism, feelings of social responsibility, pure taste for giving or even -egoistic speculation on future rewards to charity, they seriously doubt the efficiency of the market outcome. The prime reason for the presumed market failure lies in a peculiar feature of the charity market, namely: the inherent division of consumption into a material component enjoyed by the donee and a spiritual component enjoyed by the donor precisely by making somebody else better off. For other potential donors this creates the chance for a free ride: as long as their preferences for giving at least partially depend on the well-being of the recipients - pure private good cases are excluded -, they adjust far others' transfers to the poor by reducing their own contributions to an independent adjustment equilibrium level with marginal social utility greater than marginal cost of the transfers. Thus the overall level of charitable giving will remain below Samuelson's optimal public goods supply, and a case for public redistribution in the broadest sense (including the provision of Welfare services) seems to be established.
Keywords: 330